A Morphological Study of Kampung Arab, Singapore in A Century - Purwantiasning, Ari Widyati; Bahri, Saeful; Al-Amin, Roby; Setiawan, Sandy (International Journal of Built Environment and Scientific Research, 2025)
Singapore is a country with diverse cultures, histories, and traditions that blend in culture in Singapore is the Arab Village, located in the Kampong Glam district. The region is known for its rich Malay and Arabic cultural values, and has been an integral part of Singapore's cultural richness for more than a century. Over the past century, the Arab Village has undergone many transformations, both physically and socially. The area, which was once a traditional settlement, has now developed into a bustling commercial and tourist hub. These changes bring their own challenges in maintaining existing heritage values. This research uses a qualitative method with a historical research approach. The historical research approach is an approach that looks at events that occurred in the past to produce an accurate interpretation and description. The study of the morphology of the Arab Village area aims to reveal the changes that have occurred in the area over the past century. Through a morphological analysis approach, this study will examine various aspects including road networks, building typologies, and allergic use. Keywords: Kampung Arab; Kampung Glam; Morphology; Singapore